Sacco and Vanzetti : the anarchist background - Avrich, Paul.; Paul Avrich Collection (Library of Congress) (Princeton, N.J. : Princeton University Press, 1991)
An in-depth study of the lives of Nicola Sacco and Bartolomeo Vanzetti, based on anarchist sources and new materials, provides answers to crucial questions about one of the most notorious cases in American legal history. Bibliog.
Part One: Immigrants. Ch. 1. Italian childhoods -- Ch. 2. Free country -- Ch. 3. Vanzetti -- Ch. 4. Anarchists -- Ch. 5. Mexico. Part Two: Red Score. Ch. 6. Face to face with the enemy -- Ch. 7. Carlo and Ella -- Ch. 8. Deportations delirium -- Ch. 9. Go-ahead! -- Ch. 10. Plain words. Part Three: Repression. Ch. 11. Manhunt -- Ch. 12. The spy -- Ch. 13. Death of Salsedo -- Ch. 14. The arrest -- Ch. 15. Epilogue.
Includes bibliographical references (p. [249]-255) and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Sacco, Nicola, -- 1891-1927.; Vanzetti, Bartolomeo, -- 1888-1927.; Sacco, Nicola, -- 1891-1927; Vanzetti, Bartolomeo, -- 1888-1927; Sacco, Nicola, -- 1891-1927.; Vanzetti, Bartolomeo, -- 1888-1927.; Sacco, Nicola, -- (1891-1927); Vanzetti, Bartolomeo, -- (1888-1927); Anarchists -- United States -- Biography; Anarchism -- United States -- History; Sacco-Vanzetti Trial, Dedham, Mass., 1921.; Anarchistes -- États-Unis -- Biographies; Anarchisme -- États-Unis -- Histoire; Affaire Sacco et Vanzetti, Dedham, Mass., 1921.; 15.85 history of America; HISTORY -- United States -- 20th Century; Anarchism; Anarchists; Massachusetts -- Dedham; United States; Anarchismus; Sacco-Vanzetti-Fall; Politieke processen (rechtspraak); Anarchisten; Anarchistes -- États-Unis -- Biographies; Anarchisme -- États-Unis -- Histoire -- 1900-1945.; Sacco et Vanzetti, Affaire (1920-1927); 1921; Anarchism -- History; Massachusetts; collective biographies; Biographies; History; Biographies; Biographies